Infants' Temperament and Mothers', and Fathers' Depression Predict Infants' Attention to Objects Paired with Emotional Faces. - Aktar, Evin; Mandell, Dorothy; Vente, Wieke; Majdandžić, Mirjana; Raijmakers, Maartje; Bögels, Susan; Mandell, Dorothy J; de Vente, Wieke; Raijmakers, Maartje E J; Bögels, Susan M (Journal of Abnormal Child Psychology, 2016)
Between 10 and 14 months, infants gain the ability to learn about unfamiliar stimuli by observing others' emotional reactions to those stimuli, so called social referencing (SR). Joint processing of emotion and head/gaze direction is essential for SR. This study tested emotion and head/gaze direction effects on infants' attention via pupillometry in the period following the emergence of SR. Pupil responses of 14-to-17-month-old infants (N = 57) were measured during computerized presentations of unfamiliar objects alone, before-and-after being paired with emotional (happy, sad, fearful vs. neutral) faces gazing towards (vs. away) from objects. Additionally, the associations of infants' temperament, and parents' negative affect/depression/anxiety with infants' pupil responses were explored. Both mothers and fathers of participating infants completed questionnaires about their negative affect, depression and anxiety symptoms and their infants' negative temperament. Infants allocated more attention (larger pupils) to negative vs. neutral faces when the faces were presented alone, while they allocated less attention to objects paired with emotional vs. neutral faces independent of head/gaze direction. Sad (but not fearful) temperament predicted more attention to emotional faces. Infants' sad temperament moderated the associations of mothers' depression (but not anxiety) with infants' attention to objects. Maternal depression predicted more attention to objects paired with emotional expressions in infants low in sad temperament, while it predicted less attention in infants high in sad temperament. Fathers' depression (but not anxiety) predicted more attention to objects paired with emotional expressions independent of infants' temperament. We conclude that infants' own temperamental dispositions for sadness, and their exposure to mothers' and fathers' depressed moods may influence infants' attention to emotion-object associations in social learning contexts.